ANALISIS DAMPAK PENERBITAN OBLIGASI WAJIB KONVERSI (OWK) PT KRAKATAU STEEL TERHADAP EKONOMI PROVINSI BANTEN - Fachrizal Fachrizal (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2021)
This paper tries to analyze the impact of issuance of mandatory convertible bonds by PT Karakatau Steel to Banten Province’s Economics using the 2015 Banten Province’s input-output model classification of 35 sectors. The pronouncement of the issuance of mandatory convertible bonds was made as the results of the General Meeting of Shareholders on November 24th, 2020 in Jakarta. The impact of covid-19 was also felt by national steel industries including PT Karakatu Steel, where there is a decline in demand for national steel products by up to 50%. As a result of the reduced demand, many national steel industry operations have been hit and are experiencing financial difficulties. With the issuance of OWK by PT Krakatau Steel from Government Investment in the framework of this PEN Program, it is hoped that the wheels of the national economy can rise again, especially for the province of Banten where PT Karakatu Steel is located.